The development of teacher identity, emotions and practice: Before and after graduation from an MA TESOL program. (November 2018) - Nasrollahi Shahri, Mohammad Naseh
Abstract: The study explored how an ESL teacher's identity and emotions interacted with her classroom practice over time at a large US university. Multiple data sources including interviews, observations and lesson plans were collected when the participant had just started an MA TESOL program and when she had graduated from the program. Drawing on a sociocultural framework, data analysis was conducted at the three levels of microgenesis (moment-to-moment interaction), ontogenesis (teaching career over time) and sociocultural history (culture and educational context). The findings suggest that the participant saw herself as enacting critical pedagogy and exhibited an emotional attachment to this identity. This attachment was traced back to the participant's perezhivanie, that is, the emotional experience of her previous teaching context. In addition, the participant continued to identify herself as a teacher promoting critical pedagogy but the meaning of critical pedagogy developed significantly as informed by what she had learnt from the MA TESOL program. The study concludes by emphasizing the importance of supporting teacher emotions and identities in teacher education programs with pedagogical concepts to develop more effective classroom practice. It suggests that while pedagogical knowledge is important, without corresponding teacher emotions and identities, it does not necessarily produce desired teaching outcomes.